Emergence and Distribution of Diverse Serovars of Non-Typhoidal Salmonellae in Mangalore, Coastal Karnataka: A 12-year Experience - Beena Antony; Anup Kumar Shetty; Thomas S. Kuruvilla (Archives of Medicine and Health Sciences)
Background and Aim: Non-Typhoidal Salmonellae (NTS) is emerging as a major health problem globally. They cause foodborne infections, especially gastroenteritis as well as extraintestinal manifestations. As this is a zoonotic disease, certain animal sources such as poultry, egg, meat and dairy products are implicated. Fruits and vegetables too contaminated by manure of infected animal excreta are possible vehicles of transmission of this disease. The present report analyzes the spectrum of NTS with seroprofiling, isolated in our institute for the last 12 years. Materials and Methods: Fresh fecal samples from patients with acute gastroenteritis and blood samples from cases of bacteremia were processed according to the standard protocol. Nonlactose fermenting colonies resembling Salmonella were subjected to biochemical characterization and antimicrobial susceptibility testing followed by serotyping. Results: One hundred fifty-two NTS strains were isolated from feces and 13 from blood. Serotyping of these strains revealed that the most common NTS species was Salmonella Typhimurium (44.8%), followed by Salmonella Oslo (15.2%) and Salmonella Weltevreden (11.5%). Many rare strains were also encountered in our study. Conclusion: As many of the NTS species are biochemically similar, serotyping of NTS should be made mandatory to know the burden of the disease and to detect the emergence of new serovars. Emergence of multidrug resistance in NTS strains is a major concern nowadays. It is very essential to adopt strict quality measures in poultry, fish, dairy, and meat processing units as they are widely distributed in animals. In addition, strategies should be formulated by health education and public awareness programs to sensitize the population regarding this menace.